30 years experience of Mir submersibles for the ocean operations. (September 2018) - Sagalevich, Anatoly M.
Abstract: The role of deep manned submersibles (DMS) in scientific research of the ocean is considered. The history of development of DMS introduced, drawing attention on the steps, generated by submarine accident ("Thresher") and scientific research jumps (hydrothermal vents discovery). Development of the building of DMS in Russia and particular in P.P.Shirshov Institute of Oceanology RAS is considered, concentrating on world wide research with "Pisces VII" and "Pisces XI" submersibles in 70–80-s of XX century. Short description of MIR-1 and MIR-2 design is introduced, as the best 6000 m DMS in the world. The introduction of various underwater operations of DMS "Mir-1" and "Mir-2", including research of hydrothermal fields on ocean bottom, solution of important state tasks, observations and filming of deep ocean wrecks etc. are described.